Unveiling the Lived Experiences of Western Indonesian Students in Javan Higher Education Institutions: A Phenomenological Exploration - Jatmikowati, Sri Hartini (Universitas Medan Area, 2024)
This qualitative research embarks on an exploratory journey into the lived experiences of a specific group of students—young minds from western Indonesia who are embarking on an academic journey in the dynamic ecosystem of higher education institutions in Java. In the literature synthesis, it is clear that while the experiences of international students have been studied extensively, the experiences of certain subgroups within a country remain relatively unexplored. This phenomenological exploration of the life experiences of West Indonesian students in Javanese institutions not only enriches academic discourse but also informs practical strategies for enhancing the educational journey of these students. The study identified several major challenges faced by these students, including language barriers, misunderstanding of culture and social norms, variations in academic expectations, adaptation to local cuisine, and the formation of social networks. While these challenges were formidable, the narratives of these students also reveal their resilience and capacity for personal growth. These findings offer valuable insights that go beyond academia. Recommendations include establishing a standardized and accessible cultural orientation program, fostering a network of peer support, and recognizing the need for academic guidance tailored to the unique challenges facing Western Indonesian students. This research not only contributes to a deeper understanding of cross-cultural adaptation and personal growth but also has practical implications for policymakers and educational institutions.